The Effect of Oil Concentration on the Antioxidants Effectivity in Oil-In-Water Emulsion System - Feti Fatimah; Dedi Fardiaz; Nuri Andarwulan (Jurnal Teknologi dan Industri Pangan, 2005)
The oxidation of lipids in emulsified form is more complex than that in bulk lipids. In the emulsified form, there are more variables influencing lipid oxidation, including oil concentration, type and concentration of emulsifier, pH and buffer system. The aim of this research was to study the effect of corn oil concentration on antioxidant effectivity of Oil-In-Water emulsion system. The effectiveness of antioxidants in the system were determined by Rancimat. Hydroperoxides content was also determined during five days of oxidation. The polarity of antioxidant was measured by determining the partition coefficient in octanol-water system (1:1). The partition coefficient of butylated hydroxy toluene (BHT) was 10.19 (90.0%), -tocopherol was 8.44 (89.4%), t-butylhydroquinone (TBHQ) was 3.98 (79.9%), hydroquinone was 1.60 (61.5%), Trollox was 0.47 (32.0%) and gallic acid was 0.04 (4.4%). The increase of oil proportion from 10% to 50% in emulsion system improved the oxidative stability of emulsion. The lower antioxidant polarity could increase the effectiveness of antioxidant in emulsion system with 10% corn oil proportion. The effectiveness of antioxidant was not absolutely depended on the order of polar paradox. The effectiveness was more influenced by its hydrogen donating capability and physicochemical properties of the emulsion system. Key words: Antioxidant, emulsion, corn oil, polarity, partition coefficient polar paradox